Workshop Pengenalan Openmediavault Sebagai Sistem Operasi Jaringan Pada Sekolah Menengah Kejuruan (SMK) Mandiri - Saidi Ramadan Siregar; Hery Sunandar; Pristiwanto Pristiwanto (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
The development of technology in the field of computer networks in the era of the 21st century is very fast along with its rival, namely information system technology. Both of these technologies play an important role in the world of informatics because they complement each other and contribute to each other. For example, the information system already exists but the storage is still constrained, which means that the information system only runs on standalone, meaning it runs on its own device. as an operating system network attached storage is one of the data storage in a computer network where everything related to data can be stored in it including information systems that can be run through the operating system. At the level of Vocational High School (SMK) the Department of Computer Network Technology still rarely practices in making data storage using a network-based operating system. Therefore, it is necessary to make efforts to upper secondary level students, especially vocational schools majoring in computer network technology in knowing or increasing their knowledge of data storage in computer networks by utilizing open source services. Workshop is the last solution to provide direct practice to these students because in essence they are very happy with hands-on practice. In order for this workshop to run as expected and coincide with the COVID-19 pandemic, the implementing team or community service participants obey the health protocol. The practicum software media used are virtualbox, openmediavault, while the hardware is in the form of a laptop that has been provided by the Budi Darma University which has been given prior permission by the campus. The final result of this activity is that the students are able to install app templates from portainer.io